DEVELOPING TEACHING SPEAKING MEDIA BY USING CLASSDOJO APPLICATION FOR THE TENTH GRADE STUDENTS AT SMA NEGERI 3 MEDAN - Nia Fitria Sari; Indra Hartoyo; Farida Hanim Saragih (Universitas Negeri Medan, 2020)
This study aims to: (1) find out the media used in teaching speaking for the tenth grade students at SMA Negeri 3 Medan, (2) determine the media needed by tenth grade students in speaking skills, and (3) to develop the valid media for teaching speaking based on the needs of tenth grade students. The research was conducted by using the Research and Development method from Gall, Gall, and Borg (2003). The research subject was X MIA 7 students of SMA Negeri 3 Medan. The research object is to develop the teaching English media for speaking skill by using ClassDojo Application. The instrument used was student questionnaire. The data was collected using questionnaires validation sheets. The validator consists of the English lecturer and teacher. The data were analyzed using descriptive analysis. The results of the study show that: (1) the media used by teacher does not support teaching and learning processes, (2) interactive media such as ClassDojo is the media which is needed by students, and (3) the developed media have been valid with a percentage of 90% from lecturer and 86%% from the English teacher and this media is appropriate and applicable to use regarding the students' needs for speaking skills.Keywords: ClassDojo, Speaking, Research and Development (R&D), Teaching Media